Efektivitas Model Pembelajaran Kooperatif tipe TSTS terhadap Hasil Belajar Siswa Kelas VII SMPN 1 Latambaga - Yazir Hamsah; Andi Mariani Ramlan (Arus Jurnal Pendidikan, 2021)
This research is motivated by the low mathematics learning outcomes of students and teachers who do not use varied learning models and only use conventional learning models. The objectives of this study include: 1) to examine the learning outcomes of mathematics taught using the TSTS learning model for seventh grade students of SMPN 1 Latambaga?; 2) to examine the learning outcomes of mathematics taught by using conventional learning models for class VII students of SMPN 1 Latambaga?; 3) to find out whether the TSTS type of cooperative learning model is more effective than conventional learning models on the learning outcomes of class VII students of SMPN 1 Latambaga?. The experimental design carried out in this study was a Posttest-only Control Design. This research was conducted in the even semester of the 2015/2016 academic year. The population in this study were all eighth grade students of SMPN 1 Latambaga which consisted of 6 classes. Sampling in this study was carried out by purposive sampling technique. The sample consisted of 2 classes, one class as the experimental class and one class as the control class. The measure of the effectiveness or success of the implementation of the TSTS learning model on student learning outcomes can be seen from the implementation of the teacher's success in managing the classroom and student activity. Based on the results of data analysis obtained 1) the average mathematics learning outcomes of class VIIIE students who were taught using the TSTS learning model consisting of 23 students showed a minimum score of 65, a maximum value of 95, an average (mean) 75.9130, variance 64,447, and standard deviation 8.027; 2) the average mathematics learning outcomes of class VIII F students who are taught using the conventional learning model consisting of 24 students showing a minimum score of 45, a maximum value of 78, an average (mean) of 65.916, a variance of 87.732, and a standard deviation of 9.366; 3) the value of tcount = 3.921 with Sig. = 0.000 <α = 0.05, then it is rejected and H1 is accepted. With the acceptance of H1 it can be concluded that the TSTS type of cooperative learning model is more effective than the conventional learning model on the mathematics learning outcomes of eighth grade students of SMPN 1 Latambaga.